Post-pandemic and libraries: what now? - Parada, Alejandro E. (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2021)
The following editorial analyzes some aspects that may possibly occur in libraries in a post-pandemic setting. Although the bibliography on this subject is already abundant and uncontrollable and, in addition, there is a risk of falling into a prospective librarian that exceeds reality, the Editorial attempts to analyze various topics of professional interest to libraries: the need to adapt to the new times in order to survive, the adequacy of a balance between the remote and the face-to-face, the professionalization of domestic life, the crossroads of these institutions to convert themselves into teaching places, the new alliances of libraries with pedagogical purposes, the importance of reconfiguring the union identity of its professionals, among other issues. Thus, within this context, the post-pandemic constitutes a challenge to consolidate the growth of libraries and to promote new citizenship rights.